Chile-Japan, 1990-2007: Advances and Reflections in a Failed Strategic Alliance [Chile-Japón, 1990-2007: Avances y Repliegues en Una Alianza Estratégica Fallida] - Ross-Orellana, C (Universidad de Tarapaca, 2018)
In this historical period, bilateral relations were marked by the public-private decision to grant them a status of "strategies." A bilateral effort that was frustrated by the complete objective that was posted as by the extemporaneous model of the association that appealed (typical of the cold war), and that from 1990 to 2007 was faced with the frenetic speed of global economic transformation. A fundamental question to understand this paradox is why a power like Japan decides to have a strategic relationship with a country as small as Chile? And eventually, what happens when a new power is strategically coupled with a smaller state? To address this dilemma, we used two analytical methodologies elaborated ex profeso, and from their results, we can propose a new idea that can improve the understanding of this phenomenon, and by extension, of this period. The hypothesis of this paper suggests that the undervalued effect of the 1997 Asian crisis in the course of the strategic alliance agreement signed in 1994 put the project in check and that subsequent efforts to sign a TCL failed to reverse. © 2018 Universidad de Tarapaca.